Does International Financial Reporting Standards convergence promote informational efficiency? - Tee, Lain-Tze; Kew, Si-Roei (Penerbit Universiti Kebangsaan Malaysia, 2017)
This study explores a novel extension of the informational efficiency literature. We examine the impact of the convergence of International Financial Reporting Standards (IFRS) on stock price delay in the Malaysian stock market over a study period2001 to 2016. The study uses Hou and Moskowitz’s (2005) model to measure the stock price delay, an inverse indicator of informational efficiency. It is found that stocks have less delay on price adjustment to local and global market-wide information during the convergence of IFRS than before the IFRS was converged. Further, the panel data analysis is applied to test the empirical linkages between the convergence of IFRS and stock price delay. After controlling for trading volume, firm size, market volatility and financial crisis, we find strong evidence that the IFRS plays an essential role in promoting informational efficiency. Specifically, the convergence of IFRS decreases the local and global stock price delay. This is possibly due to the IFRS convergence promotes a more transparent reporting mechanism, reduces asymmetric information among market participants and thereby enhances stock price efficiency in incorporating information. The findings will be of help to policymakers in the effort to increase informational efficiency and those with interest in the subject.